The Antiquities of Constantinople : With a Description of Its Situation, the Conveniencies of Its Port, Its Publick Buildings, the Statuary, Sculpture, Architecture, and Other Curiosities of That City - Gilles, Pierre, 1490-1555 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Antiquities of Constantinople" by Pierre Gilles is a historical account written in the early 16th century. The work serves as a detailed description of the city of Constantinople, examining its history, architecture, public buildings, and the various antiquities found within. The book stands as a significant source of information about the city during a period when it was experiencing significant change, especially after the fall of the Byzantine Empire. At the start of the work, John Ball, the translator, provides both a dedication and a comprehensive preface. He highlights the importance of antiquities and the cultural richness of Constantinople, suggesting that its unique geographical position and historical significance make it a subject of essential interest. The opening chapters explore the city's founders and its establishment, detailing the evolution of its structure and architecture over time. There is a vivid description of the city's environment, noting its strategic advantages, abundant resources, and its role as a vital trade hub between Europe and Asia. This sets the stage for a thorough exploration of Constantinople's glory in subsequent chapters. (This is an automatically generated summary.)
Release date is 2016-09-18
E-text prepared by Turgut Dincer, Brian Wilcox, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org); frontispiece generously made available by the Google Books Library Project (http://books.google.com)
Keywords: Istanbul (Turkey) -- Description and travel; Turkey -- Antiquities; Istanbul (Turkey) -- Antiquities